Reaching Out for Inaccessible Food Is a Potential Begging Signal in Cooperating Wild-Type Norway Rats, Rattus norvegicus - Paulsson, Niklas I.; Taborsky, Michael (Frontiers in Psychology, 2021)
Begging is widespread in juvenile animals. It typically induces helpful behaviours in parents and brood care helpers. However, begging is sometimes also shown by adults towards unrelated social partners. Adult Norway rats (Rattus norvegicus) display a sequence of different behaviours in a reciprocal food provisioning task that have been interpreted as such signals of need. The first behaviour in this sequence represents reaching out for a food item the animal cannot obtain independently. This may reflect either an attempt to grasp the food object by itself, or a signal to the social partner communicating the need for help. To distinguish between these two possibilities, we tested in female wild-type Norway rats if the amount of reaching performed by a food-deprived rat changes with the presence/absence of food and a social partner. Focal rats displayed significantly more reaching behaviour, both in terms of number and total duration of events, when food and a potentially helpful partner were present compared to when either was missing. Our findings hence support the hypothesis that rats use reaching behaviour to signal need to social partners that can help them to obtain food.